Evolution of free fatty acid profile during ripening in cheeses manufactured from bovine, ovine and caprine milks with extracts of Cynara cardunculus as coagulant - Sousa, M. José (2011)
Changes in the concentrations of free fatty acids (FFA) in bovine, ovine and caprine milk cheeses manufactured with a plant rennet (flowers of Cynara cardunculus) were studied throughout a 68-day ripening period. The long-chain saturated (C16 : 0 and C18 : 0) and unsaturated (C18 : 1, C18 : 2, and C18 : 3) FFA were the most abundant at all stages of ripening. The overall concentration of FFA in fresh cheese was 3598, 3538 and 3868 mg/kg cheese for bovine, ovine and caprine milk cheeses, respectively; these values increased to 5047, 6517 and 5257 mg/kg cheese, respectively, by 68 days, of which 1171, 1734 and 1791 mg/kg cheese, respectively, were accounted for by C4 : 0 – C12 : 0. The FFA that showed the highest fractional increase by 68 days of ripening in bovine milk cheese were C4 : 0, C6 : 0, C8 : 0, C12 : 0, C18 : 1 and C18 : 2; in ovine milk cheese they were C4 : 0, C6 : 0, C8 : 0, C10 : 0, C14 : 0, and C18 : 1; and in caprine milk cheese they were C4 : 0, C8 : 0, C10 : 0, C14 : 0 and C18 : 1.